Uptime optimization in a vertical dryer and its economic impact - Anderson Farias da Silva; Jorge Henrique de Oliveira Sales; João Pedro de Castro Nunes Pereira (The Journal of Engineering and Exact Sciences)
Cocoa in Bahia is traditionally cultivated in agroforestry systems that make it possible to conserve the biodiversity of the Atlantic Forest via a cultivation system called cabruca. The purpose of this article is to present the method to measure the standard operating time in cocoa drying. The standard time technique, which is a resource that allows analyzing the productive capacity of a process, considering a series of aspects present in the work routine have a great impact on the time required to manufacture a product. Thereby, we investigated the difference in operating time (standard time) between two drying systems (baarcaça and vertical dryer) impacting crop productivity and financial viability in the drying process. The result found for the standard operating time of the traditional barge and the vertical cocoa dryer indicates a 63.3% reduction in the standard operating time in favor of the vertical system.